Percepción sobre el desarrollo sostenible de las MYPE en el Perú - Hernani Merino, Martín Nelson (2013)
This article assesses the perception of undergraduate students about social responsibility activities implemented by micro and small enterprises (MSEs) in Peru. This article seeks to contribute to a better understanding on how to implement programs about social responsibility in universities. To achieve this objective, a scale was built and applied to 506 college students at five universities. From the results of the study, in general terms, it can be concluded that college students have a low perception about activities of social responsibility applied by the MSES. This conclusion highlights the importance of introducing courses of social responsibility on the curricula of universities to enrich the education and new research on this topic. In consequence, it is recognized the need for an interdisciplinary approach at the theoretical level and an intradisciplinary approach at the practice level. This may ensure the creation and application of new knowledge about social responsibility towards sustainable development.